A Comparative Study of Visual Acuity in Adolescents between Pre-Pandemic Against During and After the COVID-19 Pandemic - Amanda, Elizabeth Veronica; Fajriazzafira, Fawila; Willy, Johannes; Bedu, Thomas Febrian; Salsabila, Valinka Alya; Pasaribu, Irma Andriani; Ardiana, Dian (Universitas Airlangga, 2026)
Introduction: Refractive error is one of the most prevalent visual impairments worldwide. During the Coronavirus disease (COVID-19) pandemic, prolonged school closures and social restrictions, forcing adolescents to a sharp increase in digital screen use, created ideal conditions for the progression of refractive errors. Purpose: To evaluate and compare the prevalence of refractive errors among adolescents aged 17–20 years before the pandemic, in contrast to during and after the COVID-19 pandemic. Methods: This retrospective cross-sectional study analyzed the medical records of 77 adolescents aged 17–20 years who underwent visual acuity examinations at RSPAL dr. Ramelan, Surabaya, East Java, Indonesia, between 2019 and 2025 under purposive sampling. Screen time data were collected through structured questionnaires and categorized by daily duration. Visual acuity was recorded as the average of both eyes in decimal form. Statistical analyses were performed to compare visual acuity before, during, and after the pandemic. Results: A Wilcoxon signed-rank test revealed a significant decrease in visual acuity between the pre-pandemic and during or post-pandemic periods (Z = –7.117, p < 0.001). Among the 77 adolescents analyzed, 87.0% (n = 67) experienced a decline in visual acuity, while 13.0% (n = 10) showed no change. The majority reported daily screen time of 2–4 hours (42.9%) or more than four hours (39.0%). Conclusions: Significant reductions in visual acuity were observed during and after the COVID-19 pandemic, with a mean decline from 0.52 to 0.39. These findings highlight the potential long-term impact of pandemic-related lifestyle changes on adolescent vision and support the need for preventive strategies to protect visual health in the digital era.